FinTech's Role in Shaping Household Debt Structure: Evidence from the Housing Market in China (Journal of Global Humanities and Social Sciences, 2025)
The issue of high household housing debt is a pressing concern requiring immediate attention. Drawing on insights from behavioral economics, particularly the concept of scarcity mentality, this study investigates the potential role of digital finance in amplifying household housing debt through the manipulation of funds across mental accounts, influenced by the tube effect. Empirical analysis utilizing the Beijing University Digital Inclusive Finance Index for prefecture-level cities and data from the China Household Finance Survey (CHFS) confirms a significant association between digital finance expansion and increased likelihood of households acquiring housing debt, larger debt amounts, and elevated risk of excessive debt burden. Notably, these effects vary significantly across urban-rural divides, city classifications, and income brackets. Additionally, a spatial diffusion effect of digital finance on housing debt levels is observed, with cities with advanced digital finance infrastructure impacting surrounding areas. Importantly, household financial literacy emerges as a key mitigating factor against excessive housing debt induced by digital finance growth. The study’s implications suggest the need for enhanced regulatory measures in digital finance, establishment of a comprehensive housing consumption financial framework, regional coordination in housing debt management, and promotion of household financial education.